Investigation of the Effect of Inclusive Play and Special Movement Education to Social Communication in Disadvantaged and Peer Children in Preschool (Erzurum Sample) - Sertaç Erciş; Ahmet Şirinkan; Levent Önal (Journal of Educational Issues, 2024)
The aim of this research is to investigate the effect of inclusive play and special movement education applied to disadvantaged and peer preschool children in Erzurum city center on their basic skills. 22 students (10 disadvantaged children + 12 peer group children) consisting of disadvantaged children and peer children who were educated in special education and rehabilitation centers in the city center of Erzurum and participated voluntarily. Before the study, two seminars were given to the parents of the students, which determined the purpose and objective of the research. Students participated in a specially prepared game and movement training program for 45-60 minutes, 2 days a week during the summer period. Before starting the research, an interview and observation form consisting of 10 questions was prepared for the parents of the children and the results were recorded. At the end of the 2-month (8-week) period, interviews and observations were made with the parents of the children, and the last situation was recorded and compared with the previous situation. In the first parent interviews, the results of the research; it was observed that the children hesitated to participate in the study, they do not want to get close to other children, refrain from sharing game materials and avoid playing together and do not help. While they stated that they did not comply with the game discipline, they stated that at the end of the study program, their initial negative behavior developed completely in a positive way. In expert observations; it was observed that at the beginning, the children did not want to participate in the studies, did not listen to the volunteers, acted randomly, fought over the play materials used, and avoided playing together. While they observed that they behaved randomly, it was stated that the observations developed completely positively at the end of the research process. As a result, it was concluded that inclusive play and special movement training applied to disadvantaged preschool children and peers contributed positively to the social development of children.